Implementasi Prinsip-Prinsip Syariah dalam Pengelolaan Dana di Aplikasi IFPE Syariah - Imam Wahyudi (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
In recent years, the development of Islamic financial technology (fintech) has grown rapidly, one of which is the IFPE Syariah application. However, the IFPE Syariah application still has several challenges such as compliance with sharia principles, managing risks and increasing trust in users. Therefore, the implementation of sharia principles is needed to be more effective in managing funds in the IFPE Syariah application. This study uses qualitative research methods to collect and analyze data. The author will also provide Islamic financial theories and concepts to analyze sharia principles in financial management in sharia applications. The purpose of this study is to contribute to the development of sharia finance that is more appropriate with sharia principles and meets user needs. Literature review: This study discusses several previous studies related to the implementation of sharia principles in fund management. Theoretical study: This study discusses the definition of sharia finance, the principles of sharia finance, and the implementation of sharia principles in fund management. Sharia fintech application: This study discusses the definition of sharia fintech, the development of sharia fintech in Indonesia, and the implementation of sharia principles in the MyIFPE application. Implementation challenges: This study discusses several challenges faced in implementing sharia principles in fund management, such as limited products and services, lack of standards and regulations, innovation and technology, and education and awareness.